Az integrált vállalatirányítási rendszerek gyakorlatorientált oktatásának lehetőségei - Zörög, Zoltán (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
In our accelerating world information, information flow and information disclosure are coming to the foreground to a greater extent. The world of business is changing day by day and obtaining information has several pitfalls as we can easily meet information systems that do not provide us with the piece of information expected. There are high expectations not only for the systems themselves but also for their operators, i.e. the fresh graduates who manage them. In my opinion the practice-oriented education of students is indispensable in this area, as well. While using integrated enterprise resource planning, the systematic way of thinking plays a vital role in addition to the fact that only the data that are to make a well-grounded managerial decision must be disclosed of the millions of recorded data at the right time. My paper aims at making the teaching of enterprise resource planning more practice-oriented and tailoring them to labour market expectations.